Mental health and access to healthcare among vulnerable populations in Brazil - Pérola Teixeira dos Santos; Thiago Afonso Rodrigues Melo; Patricia Melo Aguiar (O Mundo da Saúde)
Vulnerable populations, including people experiencing homelessness, LGBTQIAPN+ individuals (lesbian, gay, bisexual, transgender and transvestite, queer, intersex, asexual, pansexual, non-binary, and other gender and sexuality groups and variations), Black people, and Indigenous peoples, are more susceptible to mental disorders and face multiple barriers in accessing healthcare. However, the scientific literature still lacks a study that synthesizes findings on this topic. This work synthesized the relationship between mental health and access to healthcare among vulnerable groups in Brazil. A search was conducted in PubMed, LILACS, and Google Scholar based on the question: “What is the relationship between mental health and access to healthcare in vulnerable populations in Brazil?” A total of 578 records were identified, of which 7 met the inclusion criteria. The LGBTQIAPN+ population showed poorer access to healthcare due to financial issues and prejudice. Stigmatization, social discrimination, and lack of resources affected access to mental health services and the quality of care for the homeless population. Race/ethnicity and low educational attainment were the main factors associated with reduced access to depression diagnosis and treatment among Black individuals. Data collected on the topic in the Indigenous population were inconsistent, preventing a conclusive analysis for this group. The implementation of public policies aimed at improving the availability and quality of healthcare services for vulnerable populations is essential to reduce access inequalities in the Brazilian population and mitigate their social and economic impacts.